827: The Chronicon Salernitanum on the Muslim Conquest of Sicily - Jäckh, Theresa (My University, 2019)
The Chronicon Salernitanum represents an important account of the beginnings of the Muslim conquest of Sicily. It explains how this had been caused by a certain Euphemios, the commander of Western Sicily: his betrothed had allegedly been abducted by a Greek rival on the island. In an act of revenge, Euphemios is said to have entered into an alliance with the Aġlabid ruler of Ifrīqiya. This article contrasts the Latin narrative with extant Arabic and Greek sources, and contextualises them by reference to both historical events and broader historiographical interpretations of this conquest.
Keywords: Aghlabids, Byzantium, Greek Christians, sexual violence, gender relations, Sicily, Arabic-Islamic expansion, treason, collaboration, North Africa, Southern Italy; 900